TINJAUAN HUKUM PEMBUKTIAN TERHADAP PENYELESAIAN SENGKETA PERALIHAN STATUS HARTA PUSAKO RENDAH MENJADI HARTA PUSAKO TINGGI DI PENGADILAN: Studi Kasus Putusan Pengadilan Tinggi Padang No.121/PDT/2023/PT.PDG - Robby Yunianto Utama MS (Indra Institute Research & Publication, 2024)
The aim of this research is to test whether the considerations of judges who decide on customary land disputes in Minangkabau are perfect enough in assessing whether a land object is an implant asset, namely a low pusako which is inserted into a high pusako. This research is a case study with a review of the Law of Evidence of the Padang High Court Decision No.121/PDT/2023/PT.PDG in resolving the dispute over the transfer of the status of Pusako Tinggi assets to Pusako Tinggi assets. This research is research using a normative juridical approach, namely legal research that uses secondary data sources obtained from library materials. The research results show that the conditions that must be met so that the status of low pusako assets can be changed to high pusako are 1. There has been inheritance or maintenance from generation to generation for 3 (three) to 4 (four) generations; 2. The origin of ownership of the property is no longer in question or in other words there is no dispute regarding who has the right to the property. Regarding the legal review of evidence regarding the judge's considerations in the Padang High Court Decision No. 121/PDT//2023/PT.PDG is the possibility of negligence or error by the judge in applying imperfect evidence law.